Autophagy Modulation in Lymphocytes From COVID-19 Patients: New Therapeutic Target in SARS-COV-2 Infection - Vomero, Marta; Barbati, Cristiana; Colasanti, Tania; Celia, Alessandra Ida; Speziali, Mariangela; Ucci, Federica Maria; Ciancarella, Claudia; Conti, Fabrizio; Alessandri, Cristiano (Frontiers in Pharmacology, 2020)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is the novel coronavirus, causing coronavirus disease 2019 (CoViD-19). During virus infection, several pro-inflammatory cytokines are produced, causing the “cytokine storm”. Among these, IL-6, TNFα, and IL-1β seem to have a central role in the progression and exacerbation of the disease, leading to the recruitment of immune cells to infection sites. Autophagy is an evolutionarily conserved lysosomal degradation pathway involved in different aspects of lymphocytes functionality. The involvement of IL-6, TNFα, and IL-1β in autophagy modulation has recently been demonstrated. Moreover, preliminary studies showed that SARS-CoV-2 could infect lymphocytes, playing a role in autophagy's upregulation. Several anti-rheumatic drugs, now proposed for the treatment of CoviD-19, could modulate autophagy in lymphocytes, highlighting the therapeutic potential of targeting autophagy in SARS-CoV-2 infection.